1999
DOI: 10.1590/s0103-90161999000100017
|View full text |Cite
|
Sign up to set email alerts
|

EFEITOS DE GIBERELINAS, CITOCININAS E DO NITRATO DE POTÁSSIO, NO PROCESSO GERMINATIVO DE SEMENTES DE LIMOEIRO `CRAVO' (Citrus limonia OSBECK)

Abstract: Foram estudados os efeitos de reguladores vegetais do grupo das giberelinas e citocininas, bem como do nitrato de potássio na germinação de sementes do limoeiro `Cravo' (Citrus limonia Osbeck). O experimento foi realizado, contendo papel de filtro como substrato para a germinação das sementes, regulado à temperatura de 25oC. As sementes foram retiradas de frutos maduros no final da safra do limoeiro `Cravo', lavadas, secas à sombra e armazenadas durante 11 dias em câmara fria. Em seguida, receberam tratamento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This result can also be due to the large quantity of potassium present in the vinasse samples, as hydric and saline stresses are correlated with the excess of soluble salts, reducing the potential of water in the soil and consequently, preventing the absorption of water by seeds in general [22]. According to Leonel and Rodrigues (1999) [23], when the levels of potassium nitrate were tested in citrus seeds, the results showed a toxic potential, inhibiting their germination. Studies conducted by Gazziero et al (1991) [24] also showed that potassium nitrate did not promote the germination of Sorghum halepense seeds.…”
Section: Discussionmentioning
confidence: 99%
“…This result can also be due to the large quantity of potassium present in the vinasse samples, as hydric and saline stresses are correlated with the excess of soluble salts, reducing the potential of water in the soil and consequently, preventing the absorption of water by seeds in general [22]. According to Leonel and Rodrigues (1999) [23], when the levels of potassium nitrate were tested in citrus seeds, the results showed a toxic potential, inhibiting their germination. Studies conducted by Gazziero et al (1991) [24] also showed that potassium nitrate did not promote the germination of Sorghum halepense seeds.…”
Section: Discussionmentioning
confidence: 99%